2022
DOI: 10.1371/journal.pone.0276103
|View full text |Cite
|
Sign up to set email alerts
|

Race (black-white) and sex inequalities in tooth loss: A population-based study

Abstract: The effect of health inequalities is determined by different socioeconomic, sex, and race conditions. This study aimed to analyze the association of tooth loss with race (defined by self-reported skin color) and sex. Based on the hypothesis that the association between tooth loss and race may be modified by sex, we also aimed to evaluate possible interactions between race and sex in association with this event, in a population-based study in the city of Campinas, Brazil. A directed acyclic graph was used to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…Racial inequalities in oral health regarding tooth decay, tooth loss, pain, and the need for prostheses, to the detriment of the Black population (Black and brown) compared to white people, have already been reported in Brazil 21 , with cumulative intersectional disadvantages when considering gender, generation, and territory intersections. One study 22 showed a significant interaction between ethnicity and sex in tooth loss, with a disadvantage for Black women who had a 19% higher prevalence of tooth loss compared to white men (PR: 1.19; 95%CI: 1.05-1.34); 26% higher compared to white women (PR: 1.26; 95%CI: 1.13-1.42), and 14% higher compared to Black men (PR: 1.14; 95%CI: 1.02-1.27) 22 . On the other hand, the likelihood of never having been to the dentist is twice as high for the Black elderly population than for older white adults, and the probability of having used oral health services in the last year is lower for Black older adults compared to older white adults 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Racial inequalities in oral health regarding tooth decay, tooth loss, pain, and the need for prostheses, to the detriment of the Black population (Black and brown) compared to white people, have already been reported in Brazil 21 , with cumulative intersectional disadvantages when considering gender, generation, and territory intersections. One study 22 showed a significant interaction between ethnicity and sex in tooth loss, with a disadvantage for Black women who had a 19% higher prevalence of tooth loss compared to white men (PR: 1.19; 95%CI: 1.05-1.34); 26% higher compared to white women (PR: 1.26; 95%CI: 1.13-1.42), and 14% higher compared to Black men (PR: 1.14; 95%CI: 1.02-1.27) 22 . On the other hand, the likelihood of never having been to the dentist is twice as high for the Black elderly population than for older white adults, and the probability of having used oral health services in the last year is lower for Black older adults compared to older white adults 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Iniquidades raciais em saúde bucal em relação à cárie dental, perda dentária, dor e necessidade de prótese com prejuízo para a população negra (pretos e pardos) em relação aos brancos já foram denunciadas no Brasil 21 , com desvantagens interseccionais cumulativas quando considerados os entrecruzamentos com gênero, geração e território. Um estudo 22 mostrou uma interação significativa entre a raça e o sexo na perda de dentes, com uma desvantagem para as mulheres negras que apresentaram a prevalência da perda dentária 19% maior em comparação com homens brancos (PR: 1,19; 95%IC: 1,05-1,34); 26% maior em comparação com mulheres brancas (PR: 1,26; 95%IC: 1,13-1,42) e 14% maior comparadas aos homens negros (PR: 1,14; 95%IC: 1,02-1,27) 22 . Por outro lado, a chance de nunca ter ido ao dentista é duas vezes maior para a população idosa negra do que a de idosos brancos e a probabilidade de ter utilizado os serviços de saúde bucal no último ano é menor para os idosos negros do que para os idosos brancos 23 .…”
Section: Introductionunclassified